The Influence of Rewards and Punishments on Employee Motivation at the Koperasi Konsumen Karyawan Keluarga Besar Petrokimia Gresik (K3PG) - Wildan Armansyah; Endang Iryanti (PT FORMOSA CENDEKIA GLOBAL, 2023)
The current era is usually referred to as the era of modernization, Human Resources (HR) is an important component for the success of any organization or business. Therefore, this research identifies the effect of Reward and Punishment on employee motivation at the Petrokimia Gresik Large Family Employee Consumer Cooperative. (K3PG). This research method is quantitative by determining the sample using the slovin formula, totaling 53 respondents and distributing questionnaires with the Google Form. The analysis technique used is (PLS). The study's findings lead to the conclusion that work motivation is influenced by both reward and punishment. The findings of this study exhibit parallels with the research done by Tien Danarti Mesra (2020), which demonstrates a considerable impact of the reward variable (X1) on motivation (Y). Additionally, Dudu Badrudi (2019) asserts that punishment has a good and tangible influence on work motivation.